Astrocytes determine conditioned response to morphine via glucocorticoid receptor-dependent regulation of lactate release - Skupio, Urszula (Neuropsychopharmacology, 2019)
To date, neurons have been the primary focus of research on the role of glucocorticoids in the regulation of brain function and pathological behaviors, such as addiction. Astrocytes, which are also glucocorticoid-responsive, have been recently implicated in the development of drug abuse, albeit through as yet undefined mechanisms. Here, using a spectrum of tools (whole-transcriptome profiling, viral-mediated RNA interference in vitro and in vivo, behavioral pharmacology and electrophysiology), we demonstrate that astrocytes in the nucleus accumbens (NAc) are an important locus of glucocorticoid receptor (GR)-dependent transcriptional changes that regulate rewarding effects of morphine. Specifically, we show that targeted knockdown of the GR in the NAc astrocytes enhanced conditioned responses to morphine, with a concomitant inhibition of morphine-induced neuronal excitability and plasticity. Interestingly, GR knockdown did not influence sensitivity to cocaine. Further analyses revealed GR-dependent regulation of astroglial metabolism. Notably, GR knockdown inhibited induced by glucocorticoids lactate release in astrocytes. Finally, lactate administration outbalanced conditioned responses to morphine in astroglial GR knockdown mice. These findings demonstrate a role of GR-dependent regulation of astrocytic metabolism in the NAc and a key role of GR-expressing astrocytes in opioid reward processing.